Examining The International Relations Theory Of The Asia Pacific - Syaiful Anam (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
The question whether the IR theories used to analyse and study the Asian region particularly Asia Pacific is relevant or not remains heatedly debated within the field itself. Prominent scholars such as David C. Kang, Barry Buzan, and Peter Katszeinstein, and Amitav Acharya have argued through their works that the study of Asian region is often analysed by IR theories that is dominated by the Western knowledge and experiences. This essay hence would like to examine which theories are the most relevant and useful to depict and explain the dynamic of international relations in Asia, particularly the Asia Pacific. It argues that IR theories that cover the dynamics of international, historical and social relations of the Asian countries would likely the most useful and relevant to analysing the IR of the Asia-Pacific.